The relationship between ART adherence and smoking status among HIV+ individuals - Moreno, Jose L. (AIDS Behav, 2015)
Smoking is highly prevalent among HIV+ individuals and studies indicate that it may be associated with poor ART adherence, though the relationship is poorly understood. In addition little is known about interest in quitting among HIV+ smokers who are having adherence difficulties. We examined smoking and ART adherence among 203 HIV+ individuals enrolled in a randomized trial of interventions to increase ART adherence. Prior analyses indicated there were no overall treatment group effects. Smoking status and motivation to quit was assessed at baseline and ART adherence was assessed at week 12, 24, 36, and 48. Longitudinal generalized estimating equation analysis that controlled for treatment group revealed that smoking status was not significantly related to adherence over time. Motivation to quit was high with 58% intending to quit in the next 6 months and 25% intending to quit in the next 30 days. Findings suggest that smoking is not associated with adherence among those with adherence difficulties. However it does not diminish importance of addressing both behaviors especially given HIV+ smokers substantial interest in changing smoking behavior.